2020
DOI: 10.22146/ipas.36935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid on the growth and yield of two maize (Zea mays L.) cultivars on andisol

Abstract: One way to improve maize (Zea mays L.) production is through land extension using Andisol land. However, andisol soil has phosphate (P) fixation problem due to the high amorphous material. Hence, the use of organic material in the form of humic acid that has greater affinity to amorphous minerals is recommended to solve the problem. This research was conducted in February-May 2017 at Tri Dharma field of Faculty of Agriculture, Gadjah Mada University. The Andisol land used has a low available P category from Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…That is due to the occurrence of root development, resulting in the improvement of water efficiency and nutrient uptake. However, Prakoso et al (2020) reported that on andisol soils, the application of 5%−15% humic acid to NPK fertilizer 16:16:16 (350 Kg ha⁻¹) had the same effect as the NPK treatment without humic acid on increasing the productivity of maize, including weight of 100 seed, dry seed weight, harvest index, and length of cobs.…”
Section: Effect Of Humic Acid Application On the Growth And Productiv...mentioning
confidence: 99%
See 2 more Smart Citations
“…That is due to the occurrence of root development, resulting in the improvement of water efficiency and nutrient uptake. However, Prakoso et al (2020) reported that on andisol soils, the application of 5%−15% humic acid to NPK fertilizer 16:16:16 (350 Kg ha⁻¹) had the same effect as the NPK treatment without humic acid on increasing the productivity of maize, including weight of 100 seed, dry seed weight, harvest index, and length of cobs.…”
Section: Effect Of Humic Acid Application On the Growth And Productiv...mentioning
confidence: 99%
“…The availability of organic matter in the soil is an essential factor that directly affects soil texture and fertility. Prakoso et al (2020) stated that applying organic materials with a high affinity for amorphous minerals, such as humic acid, was excellent for cultivation on andisol soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP-36 fertilizer, which contains P and Ca, has been proven to be able to supply P nutrients to the soil, but as an amendment, this SP-36 fertilizer has not been widely studied. The good effect of SP-36 on soybean growth and yield indicates that this material can be used as a soil enhancer [9]. In variable charge soil systems such as Andisols, Inceptisols, Oxisols, and Ultisols, this phosphate can act as a material that is able to reduce the point of zero charges (ZPC) of the soil because it can neutralize positive charge soil colloids so that the ZPC value will decrease and the soil negative charge and CEC will increase [11] [17].…”
Section: Soybean Yieldsmentioning
confidence: 99%
“…Selain jarak tanam, tanaman kedelai juga membutuhkan tambahan unsur hara untuk pertumbuhan yang maksimal yang bisa di dapatkan melalui tanah maupun melalui daun, untuk membantu penyerapan unsur hara untuk proses fotosintesis 129 (Lingga and Marsono, 2001).Selain itu penambahan pupuk memiliki target untuk meningkatkan produksi dan mutu tanaman. Ketersediaan unsur hara yang lengkap dan berimbang yang dapat diserap oleh tanaman merupakan faktor yang menentukan pertumbuhan dan produksi tanaman (Prakoso, Sulistyaningsih and Purwanto, 2020).…”
Section: Pendahuluanunclassified